Evaluation of the short-term outcome of unilateral urethral mobilization for the management of bulbar urethral stricture - Ghosh, Kartik Chandra; Saha, Prodyut Kumar; Ahmed, Masud; Mahmud, Farhad; Karmaker, Uttam (International Journal of Research in Medical Sciences, 2021)
Background: In modern urology, successful male urethral reconstruction poses a continuing challenge. Methods: It was a quasi-experimental study conducted in the department of urology, Dhaka medical college hospital, Dhaka, Bangladesh between January 2010 to December 2011. 35 patients having bulbar urethral strictures admitted in the department were study participants. All the participants underwent unilateral urethral mobilization, for buccal mucosa graft urethroplasty and followed up at least six months. RGU and MCU was done when peak flow was <15 ml /sec in uroflowmetry. Urethroscopy was done at 3rd and 6th month. The statistics used to analyze the data were descriptive statistics, and the tests done were student’s t-test, chi-square test, ANOVA, and Fisher exact test. Results: The length of strictures was observed ≤3 cm among 31% (n=11) and >3 cm among 69% (n=24) patients. As the immediate postoperative outcome among the participants, we found the mean peak urinary flow rate (Qmax), 15.3±1.2 and voided urine volume (ml), 328.8±50. Finally, as the postoperative outcome after 6 months among the participants, we found the mean peak urinary flow rate (Qmax), 24.2±2.9; voided urine volume (ml), 330.8±50.1 and PVR (ml), 11.6±3.3. In this study, some potential complications were bleeding and wound infection which were found among 11.43% and 17.14% patients respectively. Conclusions: Considering the satisfactory outcomes and lower complications unilateral urethral mobilization procedure can be considered as an effective treatment method for the management of bulbar urethral stricture.